2019
DOI: 10.1186/s13014-019-1417-7
|View full text |Cite
|
Sign up to set email alerts
|

3 fraction pencil-beam scanning proton accelerated partial breast irradiation: early provider and patient reported outcomes of a novel regimen

Abstract: Background and purposeTo report dosimetry and early adverse effects, aesthetic, and patient-reported outcomes of a prospective study of 3-fraction pencil-beam scanning (PBS) proton accelerated partial irradiation (APBI).Materials and methodsEligibility included women age ≥ 50 years with estrogen receptor positive (ER+), sentinel lymph node negative invasive or in-situ breast cancer measuring ≤2.5 cm. The prescription was 21.9 Gy (RBE 1.1) in 3 daily fractions to the post-operative tumor bed with a 1 cm expansi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…Similarly, a 100 patient cohort phase II trial was recently reported demonstrating high local control, patient satisfaction, low treatment burden, and minimal dose to the heart and lung [ 65 ]. Finally, a 3-fraction regimen of proton-based APBI, reported good or excellent cosmesis in 95% of patients, but additional study is needed [ 66 ].…”
Section: Partial Breast Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a 100 patient cohort phase II trial was recently reported demonstrating high local control, patient satisfaction, low treatment burden, and minimal dose to the heart and lung [ 65 ]. Finally, a 3-fraction regimen of proton-based APBI, reported good or excellent cosmesis in 95% of patients, but additional study is needed [ 66 ].…”
Section: Partial Breast Irradiationmentioning
confidence: 99%
“…Separate cost analyses may be warranted for additional scenarios in breast cancer radiotherapy, including those with altered fractionation. For instance, partial breast irradiation has historically been offered for carefully-selected elderly patients with favorable tumor characteristics; however, providing a 3-fraction proton-based PBI treatment may also provide cost-effective treatment to a young patient by minimizing secondary malignancies and cardiac risk [ 66 ]. Despite rigorous efforts, a modern, overarching cost-effectiveness analysis incorporating changes in the duration of treatment (e.g., hypofractionation) is still needed.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…57 Another study evaluated 3 fraction proton APBI in 76 patients, demonstrating feasibility with no grade 2 or greater toxicity and 98% of patients having excellent/good cosmesis, though long-term follow-up was not available. 58 The ultimate EBRT APBI regimen would be a single fraction approach. A prospective study of 50 patients from Washington University evaluated such an approach, with 20 Gy given to the surgical bed (5 Gy at 1 cm).…”
Section: Ultrashort Partial Breast Irradiationmentioning
confidence: 99%
“…The skin dose was purposefully limited to a median maximum dose to 1 cc of the skin of 89% of the prescription dose; the heart and ipsilateral breast doses were also low at 0% and 28% of ipsilateral breast receiving ≥50% of the prescription dose, respectively. Early results have been reported, and at a median follow-up of 12 months, there have been no grade 2 or worse acute or late adverse events reported, and patient-reported cosmesis was good or excellent in 98% of patients [ 35 ].…”
Section: Proton Partial Breast Irradiationmentioning
confidence: 99%
“…While PT dosimetry is superior to other external beam PBI delivery methods, further improvements may be possible with increasing utilization of modern pencil beam scanning PT, which has increased ability to modulate dose to the skin, provide a homogeneous dose distribution, and more effectively minimize dose to nontarget tissue. Importantly, patient-reported quality of life also appears well preserved with PT PBI, with 90% of patients reporting a 7 or better QOL on a scale of 0–10, with 10 being the best QOL in the series from Mayo Clinic, and a patient satisfaction rate of treatment and results of 100% at 24 months in the study from MDACC [ 34 , 35 ].…”
Section: Proton Partial Breast Irradiationmentioning
confidence: 99%